VP37 Patient Involvement In EUnetHTA Assessments (Non-Pharma Technologies). (2019) - Ettinger, Sabine; Erdos, Judit; De Villiers, Cecilia
Abstract : Introduction: Patients can provide valuable experience on living with diseases, health-related quality of life, various therapies and relevant outcomes. Their input and perspectives can be helpful in complementing health technology assessment (HTA) processes. The European Network for HTA (EUnetHTA), funded by the European Commission, aims to further advance and standardise patient involvement processes in order to add to the quality and applicability of HTAs and to allow capability building. Methods: Different methods for patient involvement in HTAs on non-pharmaceutical technologies were tested: Patient input templates (open questions sent to relevant patient organizations, or published on EUnetHTA website); scoping meeting with patients/patient representatives; one-on-one conversation and group conversation. Applied methods depended on the scope of the HTA and other factors like timelines of HTAs and burden of disease for patients. Results: Patients were included in eight of sixteen HTAs on non-pharmaceutical technologies. Applied methods were: group conversation (n = 2), scoping meeting (n = 1), patient input templates (n = 4), one-on-one conversation (n = 2, ) and other approach (i.e. written feedback on scope n= 2). In some HTAs more than one method was used. Main reasons for not including patients were inability to identify suitable patients or tight timelines. Patients' feedback on health-related quality of life and outcome measures proved most useful in the scoping phase. Conclusions: The different approaches were useful for complementing HTA processes. Those need to be further tested and evaluated in order to formulate deeper understanding about the impact of patient involvement on HTA. Additionally, feedback from patients that were actively involved in the HTAs should be collected to further improve the involvement methods that should serve as basis for future recommendations post 2020.